Analisis Hukum Tindak Pidana pada Oknum Guru Pelaku Pencabulan terhadap Anak di Kota Bandar Lampung - Arya Oktama (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the criminal law against teachers who commit child molestation in Bandar Lampung City. The crime of child molestation is a form of sexual violence that has serious impacts not only on the physical but also on the psychological and social development of children. In the legal context, this act is regulated in the Child Protection Law, which provides a basis for law enforcement against perpetrators. The research method used is a qualitative approach with data collection techniques through in-depth interviews, direct observation, and literature studies. The research respondents consisted of law enforcement officers, psychologists, and parents of victims. The results of the study showed that the factors that trigger child molestation include a disharmonious family environment, lack of adequate sex education, and low public awareness of child protection. In terms of law enforcement, this study found that there are still various obstacles, such as lack of strong evidence, social stigma against victims, and lack of rehabilitation for both parties, both victims and perpetrators. The criminal responsibility of the perpetrators does not only include imprisonment but also the need for rehabilitation programs and social reintegration for the perpetrators to prevent the recurrence of similar crimes. This study recommends the need to increase public awareness of the importance of child protection, training for law enforcers in handling cases of child molestation, and strengthening the role of child protection institutions in providing support to victims. With these steps, it is hoped that a safer environment for children in Bandar Lampung City can be created.